2007
DOI: 10.1016/j.ijsolstr.2006.08.003
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional numerical study of mode I crack tip fields in pressure sensitive plastic solids

Abstract: In this paper, a finite element study of 3D crack tip fields in pressure sensitive plastic solids (such as polymers or metallic glasses) under mode I, small scale yielding conditions is performed. The material is assumed to obey a small strain, Extended Drucker-Prager yield condition. The roles of pressure sensitive yielding, plastic dilatancy and yield locus shape on the 3D plastic zone development and near-crack front fields are systematically studied. It is found that while pressure sensitivity leads to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…This figure confirms that stress levels drop appreciably as free surface of the specimen is approached. The above behavior is similar to that reported for isotropic plastic solids where high hydrostatic stress levels are found to prevail close to the crack tip at the mid-plane and reduce as the free surface is approached (Narasimhan and Rosakis 1990;Subramanya et al 2007). …”
Section: Contours Of Normal and Hydrostatic Stresssupporting
confidence: 87%
See 1 more Smart Citation
“…This figure confirms that stress levels drop appreciably as free surface of the specimen is approached. The above behavior is similar to that reported for isotropic plastic solids where high hydrostatic stress levels are found to prevail close to the crack tip at the mid-plane and reduce as the free surface is approached (Narasimhan and Rosakis 1990;Subramanya et al 2007). …”
Section: Contours Of Normal and Hydrostatic Stresssupporting
confidence: 87%
“…The layers of nodes are located at X 3 / h = 0.0, 0.038, 0.084, 0.14, 0.20, 0.28, 0.38, 0.5. Thus, the layers become gradually thinner as the free surface (X 3 = 0) is approached in order to capture the strong through-thickness variation of the field quantities close to the notch root (Narasimhan and Rosakis 1990;Subramanya et al 2007). …”
Section: Modeling Aspectsmentioning
confidence: 99%
“…5, is because the crack front is driven by the hydrostatic stress gradient in the FMI mechanism [37]. Further, studies on 3-D crack tip fields in elastic-plastic solids show that the hydrostatic stress distribution along the thickness direction is uniform for the predominant portion of the specimen thickness [40,41]. Argon and Salama [37] analyzed the condition for breakdown of a blunted crack front perturbed along the thickness direction into fingers owing to the positive suction gradient ahead of it.…”
Section: Fracture Mechanismmentioning
confidence: 99%
“…Basu and Van der Giessen (2002) conducted a finite deformation analysis of crack tip fields in glassy polymers using a viscoplastic constitutive model that incorporated softening as well as orientation hardening. For pressure sensitive plastic solids, Subramanya et al (2007) performed a 3D finite element analysis of mode I crack tip fields under small-scale yielding (SSY) conditions. The crack tip for MGs was studied by Tandaiya et al(2007Tandaiya et al( , 2008, by using a continuum elastic-viscoplastic constitutive theory developed by Anand and Su (2005), and it was found that these features of plastic field, in turn, are influenced by the mechanical characteristics of MGs like Poisson's ratio and pressure sensitivity.…”
Section: Introductionmentioning
confidence: 99%